Impact of VNF placements on QoE monitoring in the cloud. Issue 3 (3rd December 2018) - Dinh‐Xuan, Lam; Popp, Christian; Burger, Valentin; Wamser, Florian; Hoßfeld, Tobias
Summary: The fast growth of video streaming is responsible for a huge amount of traffic over the past few years. Because of the variety of video content on the Internet, a potential market is emerging for video providers. However, a rapid increase in video traffic and users poses challenges for network operators maintaining user expectation. To address this problem, network operators need a mechanism to monitor the quality of experience (QoE) perceived by the user. This allows reacting to quality degradation to improve the service. With the paradigm of network function virtualization, network operators are able to deploy such a video monitoring function in the cloud. In this work, we investigate the feasibility of deploying a virtual network function (VNF) for video buffer and QoE monitoring on the Amazon Web Service cloud. To this end, we implement a VNF to analyze video flows in the network by using deep packet inspection. We investigate the influence of different points of presence (PoP) in the cloud and mobile network on the performance of the VNF for monitoring video buffer and QoE. Our findings show that the accuracy of the QoE monitoring decreases with the distance of the PoP to the client. This is not only due to the delay and bottleneck between the monitoring point and the client but also due to the client mobile access network. Abstract : In this work, we investigate the feasibility of deploying a virtual network function for video buffer and quality of experience (QoE) monitoring on the Amazon Web Service cloud. Our findings show that the accuracy of the QoE monitoring decreases with the distance of the point of presence to the client.This is not only due to the delay and bottleneck between the monitoring point and the client, but also due to the client mobile access network.